STRATEGI PENGEMBANGAN KEMITRAAN KONSERVASI MELALUI AKSES PEMUNGUTAN HASIL HUTAN BUKAN KAYU DAMAR DI TAMAN NASIONAL MANUSELA - Faizah, Faizah; Maail, Rohny M.; Lelloltery, Henderina (MAKILA, 2024)
The conservation partnership of the Manusela National Park established collaboration in the form of conservation partnerships with the community in Masihulan Village through community empowerment by giving access to non-timber forest products (NTFPs). This study aimed to formulate a strategy for conservation partnership development. This research used a descriptive qualitative method. The data of this research was analyzed by descriptive qualitative analysis, SWOT analysis, and QSPM analysis to formulate and determine the priority strategy of conservation partnerships development of NTFP utilization. This research shows that the Conservation Partnership in Manusela National Park has economic, social, and ecological impacts. Based on the SWOT matrix analysis, the strategy to develop conservation partnerships in the Manusela National Park is the Strengths and Opportunities (SO) strategy. It is implemented by optimizing its strengths and taking advantage of various existing opportunities by increasing the utilization of resin potency to create creative economic development supported by the Regional Government and mentored by the staff of Manusela National Park, increasing community participation in utilizing and preserving damar trees; and raising the implementation of conservation partnerships and stakeholder cooperation. Based on the QSPM analysis, the highest score of TAS (Total Attractive Score) is 6,35, so the priority strategy to develop conservation partnerships is increasing community participation in utilizing and preserving the resin tree.